Protein deficiency and nutritional recovery modulate insulin secretion and the early steps of insulin action in rats - Latorraca, Márcia Q.; Reis, Marise A. B.; Carneiro, Everardo M. [UNESP]; Mello, Maria A. R. [UNESP]; Velloso, Licio A.; Saad, Mario J. A.; Boschero, A. Carlos (My University, 1998)
Maternal malnutrition was shown to affect early growth and leads to permanent alterations in insulin secretion and sensitivity of offspring. In addition, epidemiological studies showed an association between low birth weight and glucose intolerance in adult life. To understand these interactions better, we investigated the insulin secretion by isolated islets and the early events related to insulin action in the hind-limb muscle of adult rats fed a diet of 17% protein (control) or 6% protein [low (LP) protein] during fetal life, suckling and after weaning, and in rats receiving 6% protein during fetal life and suckling followed by a 17% protein diet after weaning (recovered). The basal and maximal insulin secretion by islets from rats fed LP diet and the basal release by islets from recovered rats were significantly lower than that of control rats. The dose-response curves to glucose of islets from LP and recovered groups were shifted to the right compared to control islets, with the half-maximal response (EC 50) occurring at 16.9 ± 1.3, 12.4 ± 0.5 and 8.4 ± 0.1 mmol/L, respectively. The levels of insulin receptor, as well as insulin receptor substrate-1 and phosphorylation and the association between insulin receptor substrate-1 and phosphatidylinositol 3-kinase were greater in rats fed a LP diet than in control rats. In recovered rats, these variables were not significantly different from those of the other two groups. These results suggest that glucose homeostasis is maintained in LP and recovered rats by an increased sensitivity to insulin as a result of alterations in the early steps of the insulin signal transduction pathway.
Keywords: Insulin receptor; Insulin receptor substrate- 1; Insulin secretion; Nutritional recovery; Rats; insulin; insulin receptor; insulin receptor substrate 1; phosphatidylinositol 3 kinase; animal tissue; disease association; dose response; female; glucose homeostasis; glucose intolerance; glucose tolerance test; insulin release; insulin sensitivity; insulin tolerance test; low birth weight; nonhuman; pancreas islet cell; protein deficiency; protein diet; protein restriction; rat; signal transduction; Animals; Blood Glucose; Dietary Proteins; Female; Fetus; Glucose; Insulin; Islets of Langerhans; Liver; Maternal-Fetal Exchange; Pregnancy; Protein Deficiency; Rats, Wistar